Stable reference genes for the measurement of transcript abundance during larval caste development in the honeybee - Cameron, Rosannah C; Duncan, Elizabeth J; Dearden, Peter K (Apidologie, 2013)
Many genes are differentially regulated by caste development in the honeybee. Identifying and understanding these differences is key to discovering the mechanisms underlying this process. To identify these gene expression differences requires robust methods to measure transcript abundance. RT-qPCR is currently the gold standard to measure gene expression, but requires stable reference genes to compare gene expression changes. Such reference genes have not been established for honeybee caste development. Here, we identify and test potential reference genes that have stable expression throughout larval development between the two female castes. In this study, 15 candidate reference genes were examined to identify the most stable reference genes. Three algorithms (GeNorm, Bestkeeper and NormFinder) were used to rank the candidate reference genes based on their stability between the castes throughout larval development. Of these genes Ndufa8 (the orthologue of a component of complex one of the mitochondrial electron transport chain) and Pros54 (orthologous to a component of the 26S proteasome) were identified as being the most stable. When these two genes were used to normalise expression of two target genes (previously found to be differentially expressed between queen and worker larvae by microarray analysis) they were able to more accurately detect differential expression than two previously used reference genes (awd and RpL12). The identification of these novel reference genes will be of benefit to future studies of caste development in the honeybee.